2023
DOI: 10.1007/s12649-022-02023-1
|View full text |Cite
|
Sign up to set email alerts
|

Production of Gallic Acid from Swietenia macrophylla Using Tannase from Bacillus Gottheilii M2S2 in Semi-Solid State Fermentation

Abstract: In this research, an industrially important enzyme tannase and product gallic acid was produced with an inexpensive novel substrate Swietenia macrophylla. Fermentation of S. macrophylla was optimized using a two-step approach: First, the traditional One variable at-a-time technique, and second, the statistical Box-Behnken design for co-production of tannase enzyme and gallic acid. This two-step method of optimization showed the highest tannase activity and gallic acid yield of 0.0497 U/mL and 225 µg/mL respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Another report observed that for B. subtilis AM1 and L. plantarum CIR1, the maximum tannase production levels were 1400 and 1239 U/L after 32 and 36 hours of fermentation, respectively while highest gallic acid release for B. subtilis AM1 was 24.16 g/L and for L. plantarum CIR was 23.73 g/L (Aguilar-Zárate et al, 2015). Borah et al (2023) documented highest tannase activity and gallic acid yield of 0.0497 U/mL and 225 µg/mL respectively by Bacillus Gottheilii M2S2.…”
Section: Estimation Of Tannase Activity and Gallic Acidmentioning
confidence: 97%
“…Another report observed that for B. subtilis AM1 and L. plantarum CIR1, the maximum tannase production levels were 1400 and 1239 U/L after 32 and 36 hours of fermentation, respectively while highest gallic acid release for B. subtilis AM1 was 24.16 g/L and for L. plantarum CIR was 23.73 g/L (Aguilar-Zárate et al, 2015). Borah et al (2023) documented highest tannase activity and gallic acid yield of 0.0497 U/mL and 225 µg/mL respectively by Bacillus Gottheilii M2S2.…”
Section: Estimation Of Tannase Activity and Gallic Acidmentioning
confidence: 97%
“…The seeds are also used in skincare (Burlando et al 2017). Moreover, the strong and durable characteristics of mahogany wood make it a popular choice for manufacturing furniture, doors, boats, and musical instruments (Borah et al 2023). Mahogany adapts well to various environments and grows quickly, forming a lush canopy.…”
Section: Introductionmentioning
confidence: 99%
“…Semi-solid-state fermentation (Semi-SSF) is a hybrid method that utilizes both an inert solid support and a smaller volume of culture medium. This technique is considered sustainable and cost-effective (Borah et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%